2014
DOI: 10.1111/vop.12196
|View full text |Cite
|
Sign up to set email alerts
|

Development of tear production and intraocular pressure in healthy canine neonates

Abstract: STT1, STT2, and IOP values increased significantly in the first weeks after birth. The results of this study indicate that separate reference values for tear production and intraocular pressure need to be established for neonatal dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
(61 reference statements)
1
8
2
1
Order By: Relevance
“…The present study, along with others (22-24), does not confirm the reports that IOP significantly changes with age (7,13,28). In our literature review, except for a study on humans (37) and a study on lions (24), none of recent studies (22,23,25,30,36) has reported a significant relationship between the sex variable and IOP. The present study confirms these findings, since no significant difference was found between the mean IOPs obtained with TonoVet ® and Tono-Pen Vet ® for male and female dogs of all ages.…”
Section: Methodscontrasting
confidence: 54%
“…The present study, along with others (22-24), does not confirm the reports that IOP significantly changes with age (7,13,28). In our literature review, except for a study on humans (37) and a study on lions (24), none of recent studies (22,23,25,30,36) has reported a significant relationship between the sex variable and IOP. The present study confirms these findings, since no significant difference was found between the mean IOPs obtained with TonoVet ® and Tono-Pen Vet ® for male and female dogs of all ages.…”
Section: Methodscontrasting
confidence: 54%
“…There have been only very limited published studies of IOP development in normal and glaucomatous immature animals. In a study of dogs, Verboven et al, (2014) found that IOP increases until the age of about 10 to 11 weeks in that species. However, similar published data are lacking for cats, a species of particular interest as a model for human PCG.…”
mentioning
confidence: 92%
“…18 The IOP in canine puppies changes significantly during the first 12 weeks of life. 19 Following surgery for corneal and lens laceration postoperative uveitis leading to hypotony might interfere with the normal development of the eye. However, to the best of our knowledge there are no studies available looking at the development of IOP in dogs older than 12 weeks or the general development of globe size during the first months of life in puppies.…”
Section: Dogsmentioning
confidence: 99%